La représentation du policier dans les téléfilms Ivoiriens - Akadje, Mathieu A. (European Scientific Journal, ESJ, 2016)
Studying the representation of the policeman in television movies, this is partly to describe the symbolical state of the public force in the Ivorian society. This symbolic goes by the embodiment of the police function through the image of a representative of the order, acting within the framework of the police institution. This study aims at identifying the essential features of the filmic representation of the policeman and get interested in the way the society relates itself its police. The qualitative method and content analysis helped to highlight the delinquency of the policeman by filmmakers. This filmic representation of the policeman appears as a mirror of the social changes that stirs the Ivorian society.